Multivariate Modulation of the Zr MOF UiO‐66 for Defect‐Controlled Combination Anticancer Drug Delivery - Abánades Lázaro, Isabel; Wells, Connor J. R.; Forgan, Ross S. (Angewandte Chemie International Edition, 2020)
Metal–organic frameworks (MOFs) are emerging as leading candidates for nanoscale drug delivery, as a consequence of their high drug capacities, ease of functionality, and the ability to carefully engineer key physical properties. Despite many anticancer treatment regimens consisting of a cocktail of different drugs, examples of delivery of multiple drugs from one MOF are rare, potentially hampered by difficulties in postsynthetic loading of more than one cargo molecule. Herein, we report a new strategy, multivariate modulation, which allows incorporation of up to three drugs in the Zr MOF UiO‐66 by defect‐loading. The drugs are added to one‐pot solvothermal synthesis and are distributed throughout the MOF at defect sites by coordination to the metal clusters. This tight binding comes with retention of crystallinity and porosity, allowing a fourth drug to be postsynthetically loaded into the MOFs to yield nanoparticles loaded with cocktails of drugs that show enhancements in selective anticancer cytotoxicity against MCF‐7 breast cancer cells in vitro. We believe that multivariate modulation is a significant advance in the application of MOFs in biomedicine, and anticipate the protocol will also be adopted in other areas of MOF chemistry, to easily produce defective MOFs with arrays of highly functionalised pores for potential application in gas separations and catalysis. Multivariate modulation: Inclusion of multiple modulators into one‐pot self‐assembly of MOFs yields UiO‐66 nanoparticles with three drugs loaded at defect sites throughout the structure, yet still sufficient porosity to postsynthetically store a fourth, selectivity‐enhancing, anticancer drug.